ABILITY OF LACTOBACILLUS PLANTARUM ONU 12 AND BACILLUS MEGATERIUM ONU 484 TO STIMULATE GROWTH OF WHEAT SEEDLINGS AND TO FORM BIOFILMS - В. С. Твердохліб; Н. В. Ліманська; К. Д. Крилова; В. О. Іваниця (Mìkrobìologìâ ì Bìotehnologìâ. Мікробіологія і біотехнологія, 2018)
Development of biological preparations for organic agriculture should include the study of interactions of microorganisms – the components of biopreparations, with representatives of natural microbiota of agrocoenoses. As a microorganism – typical representative of epiphytic and soil microbiota, species Bacillus megaterium has been selected. Aim. The study of effect of Lactobacillus plantarum ONU 12 and Bacillus megaterium ОNU 484 on germination and growth of wheat seedlings. Materials and Methods. Seeds of wheat Triticum aestivum L. were inoculated with suspensions of bacteria B. megaterium ОНУ 484, L. plantarum ОНУ 12 and their mixture was germinated in hydroponics and soil under green house conditions. Germination of seeds, mean length of roots and height of seedlings were compared. Capability of these microorganisms to form biofilms was studied: inoculated seedlings were dyed with 0.1% acridin orange and observed with a magnification х600. Results. Simultaneous inoculation with bacteria L. plantarum ONU 12 and with the representatives of soil microbiota B. megaterium ОNU 484 didn’t decrease the stimulation effect of lactobacilli. Opposite, the highest stimulation effect on plants both in hydroponics and in soil caused the treatments with the mixture L. plantarum ONU 12 + B. megaterium ONU 484 and with the strain B. megaterium ONU 484 alone. In hydroponics mean length of roots increased in 8.0 – 16.9%, mean height of seedlings – in 8.8 – 24.3%. In soil germination of seeds increased in 7.0%, mean height of seedlings – in 7.6%, mean root length – in 13.1%. Lactobacilli and bacilli in the mixture were able to form biofilms with a developed matrix. Conclusions. In presence of representative of soil microbiota B. megaterium ONU 484 phytostimulation the activity of lactobacilli increased. Strain B. megaterium ONU484 also showed stimulation activity when applied separately.